Additively-manufactured PEEK/HA porous scaffolds with excellent osteogenesis for bone tissue repairing. (1st March 2022) - Zheng, Jibao; Zhao, Huiyu; Ouyang, Zhicong; Zhou, Xinying; Kang, Jianfeng; Yang, Chuncheng; Sun, Changning; Xiong, Minjian; Fu, Maoqing; Jin, Dadi; Wang, Ling; Li, Dichen; et al.
Abstract: Because of the good heat stability and similar mechanical properties to natural bone, polyetheretherketone (PEEK) was widely used in preparation of prosthesis. While the chemical inertness limited its osseointegration with the adjacent host bone. In this work, PEEK/HA scaffolds with hydroxyapatite (HA) contents of 0, 20%wt and 40%wt were fabricated by fused filament fabrication (FFF) process to improve osteointegration with the host bone. The cell experiment showed that the adhesion, proliferation, osteogenic differentiation and mineralization ability of BMSCs on the PEEK/HA scaffolds were significantly improved. Micro-CT results showed that PEEK/HA scaffold exhibited a higher bone ingrowth volume than those of pure PEEK scaffold. Specially, the ingrowth volume (24.3%) of 40%HA/PEEK scaffold after implantation for 12 weeks was comparable to the bone ingrowth reported for metallic or ceramic scaffolds. A smaller clearance between the PEEK/HA scaffolds and bone was found by histological staining, demonstrating a better osteointegration effect of PEEK/HA scaffold. The push-out tests result showed that PEEK/HA composites scaffolds exhibited higher bonding strength than that of the pure PEEK scaffold. In conclusion, the increased bioactivity and higher surface roughness of PEEK/HA scaffolds by introducing HA, achieved high level of bone ingrowth volume and mechanical interlocking between the scaffolds and bone. Highlights: Bioactive PEEK/HA composites scaffolds with interconnected microporous structure were printed by FFF process. The bone formation within the PEEK/HA scaffold was promoted and gap between host bone and PEEK/HA scaffolds was reduced. The bonding strength between the PEEK/HA scaffold and host bone was greatly improved.